Cultural and social accomplishments of agricultural companies as contributions to the development of rural areas - Maier, Petra; Homolka, Jaroslav; Darabos, Éva; Tikász, Ildikó; Pető, Károly; Nagy, Adrián (Applied Studies in Agribusiness and Commerce, 2009)
Agricultural companies play a key role in enriching the cultural and social life of the rural areas in which they function. Therefore, these companies serve towards preserving a quality of life necessary for rural communities to survive and to develop rural areas. However, the financial, human resource and material expenditures necessary to sustain rural communities are difficult to quantify. These studies, on the basis of internationally focused case studies, attempt to measure, systemize and evaluate the charitable engagement of farmers.